2020
DOI: 10.3390/w12113183
|View full text |Cite
|
Sign up to set email alerts
|

Surface Nuclear Magnetic Resonance Monitoring Reveals Karst Unsaturated Zone Recharge Dynamics during a Rain Event

Abstract: Understanding karst unsaturated zone (UZ) recharge dynamics is crucial for achieving sustainable management of karst hydrosystems. In this paper, we provide the first report of the application of surface nuclear magnetic resonance (SNMR) monitoring of a karst UZ during a typical Mediterranean rain event. This 79 days’ SNMR monitoring is a part of a more than 2 years of SNMR monitoring at the Low Noise Underground Laboratory (LSBB) experimental site located within the Fontaine de Vaucluse karst hydrosystem (sou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…Our data do not show fast water flow during and immediately after heavy rain events reported by Mazzilli et al, (2020). In order to better analyze large and small rainfall effects, and provide the necessary constrains to what appears as a non-linear flow modelling, we recommend a dense sampling rate during intensive rainfall events.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Our data do not show fast water flow during and immediately after heavy rain events reported by Mazzilli et al, (2020). In order to better analyze large and small rainfall effects, and provide the necessary constrains to what appears as a non-linear flow modelling, we recommend a dense sampling rate during intensive rainfall events.…”
Section: Discussionmentioning
confidence: 89%
“…When not saturated, this formation has a low storage capacity, which could explain the MRS results. Indeed, Mazzilli et al (2020) report the MRS monitoring of a heavy rain event in a karst environment. The authors observed a large MRS signal only during a few days after the rain event.…”
Section: Discussionmentioning
confidence: 99%
“…The upper formations (≈300 m thick; Figure 1) are lower Aptian/upper Barremian sub‐reef limestones (Masse & Fenerci‐Masse, 2011) with high porosities (5%–20% in the study area, Léonide et al., 2014). Seasonal variations in water content, measured by MRS (magnetic resonance sounding), revealed the strong capacitive hydrogeological role of this limestone (Carrière et al., 2016; Mazzilli et al., 2020). The underlying formations are lower Barremian limestones with significantly lower porosities (<5%; Guglielmi, 2010; Masse, 1969).…”
Section: Methodsmentioning
confidence: 99%
“…Development of multi-channel instruments has also allowed to access from 1D to 2D and 3D measurements [43]. Although the poor signal to noise ratio limits this method [42], it has proven its efficiency for limestone VZ and karstic aquifer characterization [7,[45][46] -Seismic refraction methods [47][48][49] are best applied to the characterization of tabular objects such as soil layers or horizontal cracks [5]. They also provide insights into water saturation for groundwater modeling [47] or into deep formations [39].…”
Section: Interest Of a Multi-geophysical Approachmentioning
confidence: 99%